2011
DOI: 10.1007/s00592-011-0322-9
|View full text |Cite|
|
Sign up to set email alerts
|

Miglitol administered before breakfast increased plasma active glucagon-like peptide-1 (GLP-1) levels after lunch in patients with type 2 diabetes treated with sitagliptin

Abstract: We recently reported that the administration of miglitol alone just before breakfast improved postprandial hyperglycemia and increased active glucagon-like peptide-1 (GLP-1) levels after lunch in men without diabetes. Miglitol and dipeptidyl peptidase-4 inhibitors, such as sitagliptin, enhance plasma active GLP-1 concentrations via different mechanisms; therefore, combined therapy with these agents was more effective than monotherapy. In this study, we compared the effectiveness of the administration of miglit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
25
2

Year Published

2013
2013
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 31 publications
2
25
2
Order By: Relevance
“…The effects of miglitol, vildagliptin, and their combination on plasma glucose and serum insulin were consistent with our previous report [10,11]. The absence of an increase in serum insulin levels in the V and M+V groups might be favorable for sparing insulin secretion by β cells in individuals with NGT.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…The effects of miglitol, vildagliptin, and their combination on plasma glucose and serum insulin were consistent with our previous report [10,11]. The absence of an increase in serum insulin levels in the V and M+V groups might be favorable for sparing insulin secretion by β cells in individuals with NGT.…”
Section: Discussionsupporting
confidence: 91%
“…By contrast, the administration of miglitol alone increased the AUC of the total PYY level. Based on the results of the present study, the combination therapy did not appear to have any effect on intestinal appetite regulation hormones, such as total PYY, CCK, active ghrelin, and obestatin, unlike the previously reported additive increase in active GLP-1 levels [10,11].…”
Section: Discussioncontrasting
confidence: 69%
See 2 more Smart Citations
“…In addition, it is also suggested that although the agents are usually administered thrice a day, only a once-daily administration might have some efficacy on glycemic control [33]. However, all of these studies were performed for only a several days.…”
mentioning
confidence: 99%